Preparation method of infiltration type electrical contact product
Through internal oxidation method and electrolysis process, the problems of complex and unstable quality of existing electrical contact materials are solved, and the preparation of electrical contact materials with high strength, wear resistance and oxidation resistance are achieved, reducing production costs and Environmental impact.
Patent Information
- Application Number
- CN202411654806.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-07
AI Technical Summary
The existing electrical contact materials have complex preparation processes and many types of equipment, which leads to unstable product quality.
The internal oxidation method is used to treat high-melting metal powders through chemical erosion to form a uniform and dense structure, and then the silver metal oxide is formed at a relatively low temperature through the electrolysis process, and finally melting, repressing and post-treatment are carried out.
It improves the mechanical strength, wear resistance and oxidation resistance of electrical contact materials, reduces the risks of energy consumption and environmental pollution, and improves production efficiency and product performance stability.
Smart Images

Figure CN119388060A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a melt-infiltration type electric contact product, and belongs to the field of electric contact materials. Background Art
[0002] The electrical contact is the heart of the electrical switch, responsible for the disconnection and connection of electricity, to achieve the purpose of transmitting, bearing, disconnecting and controlling energy. The reliability, durability and stability of the high-voltage electrical contact under the combined effects of high voltage, high current and high temperature arc are key factors affecting the life of the switch, safety and reliability, and the stability of the power grid.
[0003] Tungsten, tungsten carbide, molybdenum and other metals have the characteristics of high hardness, high density, high melting point, low electrical conductivity and low burnout rate. They are combined with high conductivity and low melting point metal materials to obtain high reliability contact products. Traditional silver tungsten, copper tungsten or silver molybdenum materials are mainly mixed powder infiltration process to ensure high density of electrical contact products and strong resistance to arc burnout.
[0004] For example, the invention with publication number CN108015276A discloses a method for preparing a silver-based electrical contact material with enhanced phase gradient distribution, which is characterized in that it comprises the following steps: a first step, high-energy ball milling of silver powder, enhanced phase powder and additive X powder to prepare a composite powder with silver and additive X coated on the surface of the enhanced phase powder, wherein X is any element that can be wetted with the enhanced phase and cannot be infinitely mutually soluble with silver; a second step, mixing and sieving the composite powder obtained in the first step with silver powder, adding silver powder for wet mixing, and adding a colloid for powder granulation; a third step, drying, granulating and molding the wet mixed powder to obtain a blank; the molding adopts at least two steps of pressing, each step of pressing forms a layer, and the layers are arranged from large to small according to density; a fourth step, degumming and infiltrating the blank to obtain an enhanced phase gradient distribution infiltration silver-based electrical contact material.
[0005] See also Figure 1 The production process is mainly to pre-treat low-melting-point metal powder and high-melting-point metal powder to reduce agglomeration, and then mix powder - granulate - initial pressing - melt infiltration - re-pressing - post-treatment, and finally get the product. From the process point of view, the above production process has many steps, many types of equipment are invested, and there are many factors that cause unstable product quality. Summary of the invention
[0006] The purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide a method for preparing a melt-infiltration type electrical contact product.
[0007] An internal oxidation method silver metal oxide electrical contact material comprises the following steps:
[0008] S1, subjecting high melting point metal powder a to chemical etching treatment, and then washing and drying to obtain powder a1;
[0009] S2, pressing the powder a1 into a block a2 using a press;
[0010] S3, using the block a2 as the cathode of the electrolytic cell, preparing the electrolytic mother solution with the low-melting-point metal b1, and using the high-purity low-melting-point block metal b2 as the anode, and applying power for electrolysis;
[0011] S4, after several hours of electrolysis, the power is turned off and the cathode block metal ab mixture is taken out of the electrolytic cell;
[0012] S5, washing and drying the bulk metal ab mixture and cutting it into product size by laser;
[0013] S6. The cut products are subjected to melt infiltration, re-pressing and post-processing to obtain the desired finished products.
[0014] After the high melting point metal powder is treated with chemical etching, surface impurities can be removed, the activity of the reaction can be enhanced, and uniform and stable silver metal oxide can be formed in the subsequent electrolysis process. By pressing the powder into a block, a uniform and dense structure is formed, which helps to improve the mechanical strength and wear resistance of the electrical contact material and adapt to the high-load working environment. The use of low melting point metals to prepare the electrolytic mother solution allows the internal oxidation process to be carried out at a relatively low temperature, reducing energy consumption, while also reducing the thermal stress on the equipment and improving production efficiency. Subsequent infiltration, re-pressing and post-processing steps can ensure the performance and stability of the final product. Infiltration can enhance the stability and oxidation resistance of the material, while re-pressing further improves its density and corrosion resistance. Compared with the traditional preparation process of electrical contact materials, the internal oxidation method often has a lower environmental pollution risk and higher resource utilization efficiency, which helps to achieve a more sustainable production model. The use of laser cutting technology to size cut the bulk metal ab mixture can achieve high-precision and complex shape processing to meet the needs of different application scenarios. The method can adjust the composition and structure of the electrolytic material according to different needs, has good flexibility, and can provide customized solutions for electrical contact materials under different usage conditions.
[0015] Preferably, in step S1, the high melting point metal powder a is one or more of tungsten, molybdenum, tungsten carbide and the like.
[0016] Materials such as tungsten, molybdenum and tungsten carbide have extremely high melting points, which enable them to maintain excellent physical and chemical stability in high-temperature working environments. This high-temperature resistance is essential for the reliability of electrical contact materials in high-load and high-temperature applications. These high-melting-point metal powders have excellent mechanical properties, such as high hardness and high compressive strength. This ensures that the electrical contacts are not easily damaged when subjected to mechanical impact and wear, extending their service life. Tungsten and molybdenum have better oxidation resistance than many metal materials. Using these materials as the matrix of electrical contacts can improve the oxidation resistance of the entire contact and reduce the risk of failure in an oxidizing environment. The use of a variety of materials such as tungsten, molybdenum, and tungsten carbide allows flexible configuration during the production process according to different application requirements to obtain the best performance match. For example, for the selection and optimization of special environmental conditions. When current passes through, the use of high-melting-point materials can reduce the probability of melting on the surface of the electrical contact, prevent the electrical contact from welding during operation, and thus improve the stability of the electrical contact. After chemical etching, the microstructure of tungsten, molybdenum or tungsten carbide is improved, which can further increase the density and uniformity of the electrical contact material. This uniformity contributes to the effectiveness of the subsequent electrolysis process and the performance of the final product. By combining a variety of high melting point metals such as tungsten, molybdenum and tungsten carbide, composite electrical contact materials with different performance characteristics can be designed through reasonable proportions to meet the special needs of different industrial applications.
[0017] Preferably, in step S1, the chemical etching treatment is performed using hot concentrated nitric acid for 0.1-5 minutes.
[0018] Hot concentrated nitric acid can effectively remove oxides, dirt and other impurities on the surface of high melting point metal powders, ensuring the surface cleanliness during the subsequent electrolysis process. This helps to improve the electrolysis effect and the purity of the final product. After being treated with hot concentrated nitric acid, the surface of the high melting point metal will be activated, increasing the metal surface area, thereby increasing its reactivity during the electrolysis process. This helps to form a good electrical contact material. Selecting a treatment time of 0.1-5 minutes can be precisely controlled according to the properties of different metal powders and the degree of cleanliness to be achieved, optimize the treatment effect, and avoid excessive erosion leading to metal loss. Through reasonable chemical etching, the microstructure of the high melting point metal can be made more uniform and stable, thereby improving the quality of the silver metal formed during the electrolysis process and enhancing the reliability of the subsequent process. The treatment method of hot concentrated nitric acid has a good record in materials science research, establishes a scientific basis for the development of electrical contact materials, and helps to obtain repeatability and consistency in the preparation process. Chemical etching treatment is simpler than mechanical removal, and can obtain the required surface conditions in a shorter time, reducing the overall processing difficulty and environmental impact. The surface of the cleaned high-melting-point metal powder is smoother and more uniform, which is conducive to the formation of uniform current distribution during the electrolytic deposition process, thereby improving the overall density and uniformity of the electrical contact material. Hot concentrated nitric acid can moderately modify the microstructure of the metal powder surface, providing a better foundation for subsequent infiltration, re-pressing and other steps, and promoting the improvement of the conductivity, wear resistance and oxidation resistance of the final product.
[0019] Preferably, in step S2, the thickness of the block a2 pressed is the required product size thickness.
[0020] Directly pressing the block a2 to the required product size and thickness can ensure high consistency between the finished product and the design specifications, reduce the need for subsequent processing, and improve production efficiency. Through accurate thickness pressing, the raw materials can be maximized, waste generation can be reduced, which helps to reduce production costs and improve resource utilization efficiency. The pressing process can effectively enhance the density and uniformity of the material, thereby improving the mechanical properties of the block a2 while maintaining an appropriate thickness, and enhancing its strength and wear resistance. By setting the pressing thickness in a targeted manner, a more uniform microstructure can be formed in the subsequent infiltration and re-pressing processes, thereby improving the conductivity, wear resistance and oxidation resistance of the electrical contact material.
[0021] Preferably, in step S3, the current density of the electrolytic cell is 50-500A / m 2 .
[0022] Controlled at 50-500A / m 2Within the current density range, a relatively ideal electrolysis rate can be achieved, thereby improving the deposition rate of silver metal and the overall electrolysis efficiency, and shortening the production time. Appropriate current density helps to improve the uniformity and density of the electrolysis product. Too high a current density may lead to uneven deposition or the appearance of particles and pores, while too low a current density may prolong the reaction time and affect the overall performance of the material. The choice of current density can regulate the phase structure of silver metal and its oxides formed during the electrolysis process, which helps to obtain the desired phase properties, thereby achieving the optimal design of the material. Under a reasonable current density, the deposited silver metal will exhibit good conductivity and wear resistance, which helps to improve the performance and service life of the electrical contact. The setting of current density makes the electrochemical reaction process more stable and controllable, thereby reducing the unstable factors that may occur during the electrolysis process, such as bubble generation, precipitation, etc. This current density range provides flexibility for different composition and structure settings, and can provide flexible adjustment for the electrolysis process of electrical contact materials of different shapes and volumes, so that the production process can adapt to diverse needs. At the optimal current density, the deposited silver not only has excellent electrical conductivity, but also helps to improve the density and high temperature resistance of silver metal, thereby optimizing the overall performance of the final product.
[0023] Preferably, in step S3, the low melting point metal is one or more of silver, copper, gold and the like.
[0024] Silver, copper and gold are metals with very high electrical conductivity. Choosing these metals as low melting point metals helps to ensure the excellent electrical conductivity of electrical contact materials and improve the working efficiency and reliability of electrical contacts. Low melting point metals such as silver and copper can quickly melt and infiltrate high melting point metal powders during the electrolysis process to form a good interface and promote faster deposition, which is crucial for the formation of electrical contact materials. Silver, copper and gold are relatively stable in various chemical environments, especially silver, which shows good oxidation resistance in certain environments, which helps to extend the service life of electrical contacts and reduce failure rates. The combination of silver, copper and gold can form different alloys to regulate the properties of the materials, such as optimizing wear resistance, oxidation resistance and conductivity by adjusting the proportion of components to meet the needs of different applications. Metals such as silver and copper have excellent plasticity and ductility, which helps to obtain electrical contact materials that are easier to change shape and process during processing and processing, thereby improving production flexibility.
[0025] Preferably, in step S4, after the electrolysis stops, a silver layer is coated on the surface of the bulk metal ab mixture, and the thickness of the silver layer is calculated according to the actual product composition.
[0026] The presence of the silver layer significantly improves the conductivity of the electrical contact material, enhances the efficiency of electron transmission, ensures more stable electrical contact performance, and meets the requirements of electrical equipment for electrical conductivity. As a low-melting-point metal, silver can effectively improve the wear resistance, corrosion resistance and oxidation resistance of the entire composite material, improve the overall performance of the electrical contact, and extend its service life. The thickness of the silver layer is calculated according to the actual product composition and can be flexibly adjusted to meet the requirements for conductivity, wear resistance and oxidation resistance in different applications, thereby achieving precise design and optimization. The silver layer can effectively isolate the high-melting-point metal below from contact with the environment, prevent the intrusion of oxygen and corrosive substances, and thus improve the material's oxidation resistance in high temperature or harsh environments. The silver layer can not only improve the physical properties of the material, but also increase the beauty of the product, enhance market competitiveness, and meet customer requirements for appearance quality. The deposition of the silver layer can increase the surface hardness of the bulk metal ab mixture, reduce wear and mechanical damage, and improve the reliability of the product in the working environment. The silver layer may form a certain degree of alloying at the interface with the high melting point metal, which improves the interfacial bonding strength of the electrical contact and helps to ensure the stability and durability of the product under high load conditions.
[0027] The beneficial effects of the present invention are as follows: firstly, the high melting point metal powder is subjected to chemical etching treatment to increase the roughness of the powder surface and improve the powder pressing formability. Then, the pressed high melting point metal block is immersed in an electrolyte. Through the action of electric current, the low melting point metal will continuously precipitate from the electrolyte and fill into the pores of the high melting point metal block. Moreover, a layer of low melting point metal is electrolytically attached to the surface of the high melting point metal block, replacing the operation of placing low melting point metal sheets in the traditional process. Finally, the mixed metal block is taken out from the electrolytic cell, and the desired finished product can be obtained through cleaning, drying, slitting, infiltration, re-pressing and post-processing. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, without paying creative labor, other drawings obtained based on these drawings still belong to the scope of the present invention.
[0029] Figure 1 This is the process flow chart of the traditional powder mixing infiltration process;
[0030] Figure 2 is a process flow chart of the present invention;
[0031] Figure 3 This is a metallographic diagram of the AgW65 product of the present invention;
[0032] Figure 4This is the metallographic diagram of the AgWC50 product of the present invention. DETAILED DESCRIPTION
[0033] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.
[0034] It should be noted that all expressions using "first" and "second" in the embodiments of the present invention are for distinguishing two non-identical entities with the same name or non-identical parameters. It can be seen that "first" and "second" are only for the convenience of expression and should not be understood as limitations on the embodiments of the present invention. The subsequent embodiments will not explain this one by one.
[0035] The directions and positions mentioned in the present invention, such as "upper", "lower", "front", "back", "left", "right", "inside", "outside", "top", "bottom", "side", etc., are only for reference to the directions or positions of the drawings. Therefore, the directions and positions used are for explaining and understanding the present invention, but not for limiting the scope of protection of the present invention.
[0036] An internal oxidation method silver metal oxide electrical contact material comprises the following steps:
[0037] S1, subjecting high melting point metal powder a to chemical etching treatment, and then washing and drying to obtain powder a1;
[0038] S2, pressing the powder a1 into a block a2 using a press;
[0039] S3, using the block a2 as the cathode of the electrolytic cell, preparing the electrolytic mother solution with the low-melting-point metal b1, and using the high-purity low-melting-point block metal b2 as the anode, and applying power for electrolysis;
[0040] S4, after several hours of electrolysis, the power is turned off and the cathode block metal ab mixture is taken out of the electrolytic cell;
[0041] S5, washing and drying the bulk metal ab mixture and cutting it into product size by laser;
[0042] S6. The cut products are subjected to melt infiltration, re-pressing and post-processing to obtain the desired finished products.
[0043] In step S1, the high melting point metal powder a is one or more of tungsten, molybdenum, tungsten carbide and the like.
[0044] Materials such as tungsten, molybdenum and tungsten carbide have extremely high melting points, which enable them to maintain excellent physical and chemical stability in high-temperature working environments. This high-temperature resistance is essential for the reliability of electrical contact materials in high-load and high-temperature applications. These high-melting-point metal powders have excellent mechanical properties, such as high hardness and high compressive strength. This ensures that the electrical contacts are not easily damaged when subjected to mechanical impact and wear, extending their service life. Tungsten and molybdenum have better oxidation resistance than many metal materials. Using these materials as the matrix of electrical contacts can improve the oxidation resistance of the entire contact and reduce the risk of failure in an oxidizing environment. The use of a variety of materials such as tungsten, molybdenum, and tungsten carbide allows flexible configuration during the production process according to different application requirements to obtain the best performance match. For example, for the selection and optimization of special environmental conditions. When current passes through, the use of high-melting-point materials can reduce the probability of melting on the surface of the electrical contact, prevent the electrical contact from welding during operation, and thus improve the stability of the electrical contact. After chemical etching, the microstructure of tungsten, molybdenum or tungsten carbide is improved, which can further increase the density and uniformity of the electrical contact material. This uniformity contributes to the effectiveness of the subsequent electrolysis process and the performance of the final product. By combining a variety of high melting point metals such as tungsten, molybdenum and tungsten carbide, composite electrical contact materials with different performance characteristics can be designed through reasonable proportions to meet the special needs of different industrial applications.
[0045] In step S1, the chemical etching treatment is performed by using hot concentrated nitric acid for 0.1-5 minutes.
[0046] Hot concentrated nitric acid can effectively remove oxides, dirt and other impurities on the surface of high melting point metal powders, ensuring the surface cleanliness during the subsequent electrolysis process. This helps to improve the electrolysis effect and the purity of the final product. After being treated with hot concentrated nitric acid, the surface of the high melting point metal will be activated, increasing the metal surface area, thereby increasing its reactivity during the electrolysis process. This helps to form a good electrical contact material. Selecting a treatment time of 0.1-5 minutes can be precisely controlled according to the properties of different metal powders and the degree of cleanliness to be achieved, optimize the treatment effect, and avoid excessive erosion leading to metal loss. Through reasonable chemical etching, the microstructure of the high melting point metal can be made more uniform and stable, thereby improving the quality of the silver metal formed during the electrolysis process and enhancing the reliability of the subsequent process. The treatment method of hot concentrated nitric acid has a good record in materials science research, establishes a scientific basis for the development of electrical contact materials, and helps to obtain repeatability and consistency in the preparation process. Chemical etching treatment is simpler than mechanical removal, and can obtain the required surface conditions in a shorter time, reducing the overall processing difficulty and environmental impact. The surface of the cleaned high-melting-point metal powder is smoother and more uniform, which is conducive to the formation of uniform current distribution during the electrolytic deposition process, thereby improving the overall density and uniformity of the electrical contact material. Hot concentrated nitric acid can moderately modify the microstructure of the metal powder surface, providing a better foundation for subsequent infiltration, re-pressing and other steps, and promoting the improvement of the conductivity, wear resistance and oxidation resistance of the final product.
[0047] In step S2, the thickness of the block a2 is pressed to the required product size thickness.
[0048] Directly pressing the block a2 to the required product size and thickness can ensure high consistency between the finished product and the design specifications, reduce the need for subsequent processing, and improve production efficiency. Through accurate thickness pressing, the raw materials can be maximized, waste generation can be reduced, which helps to reduce production costs and improve resource utilization efficiency. The pressing process can effectively enhance the density and uniformity of the material, thereby improving the mechanical properties of the block a2 while maintaining an appropriate thickness, and enhancing its strength and wear resistance. By setting the pressing thickness in a targeted manner, a more uniform microstructure can be formed in the subsequent infiltration and re-pressing processes, thereby improving the conductivity, wear resistance and oxidation resistance of the electrical contact material.
[0049] In step S3, the electrolytic cell current density is 50-500A / m 2 .
[0050] Controlled at 50-500A / m 2Within the current density range, a relatively ideal electrolysis rate can be achieved, thereby improving the deposition rate of silver metal and the overall electrolysis efficiency, and shortening the production time. Appropriate current density helps to improve the uniformity and density of the electrolysis product. Too high a current density may lead to uneven deposition or the appearance of particles and pores, while too low a current density may prolong the reaction time and affect the overall performance of the material. The choice of current density can regulate the phase structure of silver metal and its oxides formed during the electrolysis process, which helps to obtain the desired phase properties, thereby achieving the optimal design of the material. Under a reasonable current density, the deposited silver metal will exhibit good conductivity and wear resistance, which helps to improve the performance and service life of the electrical contact. The setting of current density makes the electrochemical reaction process more stable and controllable, thereby reducing the unstable factors that may occur during the electrolysis process, such as bubble generation, precipitation, etc. This current density range provides flexibility for different composition and structure settings, and can provide flexible adjustment for the electrolysis process of electrical contact materials of different shapes and volumes, so that the production process can adapt to diverse needs. At the optimal current density, the deposited silver not only has excellent electrical conductivity, but also helps to improve the density and high temperature resistance of silver metal, thereby optimizing the overall performance of the final product.
[0051] In step S3, the low melting point metal is one or more of silver, copper, gold and the like.
[0052] Silver, copper and gold are metals with very high electrical conductivity. Choosing these metals as low melting point metals helps to ensure the excellent electrical conductivity of electrical contact materials and improve the working efficiency and reliability of electrical contacts. Low melting point metals such as silver and copper can quickly melt and infiltrate high melting point metal powders during the electrolysis process to form a good interface and promote faster deposition, which is crucial for the formation of electrical contact materials. Silver, copper and gold are relatively stable in various chemical environments, especially silver, which shows good oxidation resistance in certain environments, which helps to extend the service life of electrical contacts and reduce failure rates. The combination of silver, copper and gold can form different alloys to regulate the properties of the materials, such as optimizing wear resistance, oxidation resistance and conductivity by adjusting the proportion of components to meet the needs of different applications. Metals such as silver and copper have excellent plasticity and ductility, which helps to obtain electrical contact materials that are easier to change shape and process during processing and processing, thereby improving production flexibility.
[0053] In step S4, after the electrolysis stops, a silver layer is coated on the surface of the bulk metal ab mixture, and the thickness of the silver layer is calculated according to the actual product composition.
[0054] The presence of the silver layer significantly improves the conductivity of the electrical contact material, enhances the efficiency of electron transmission, ensures more stable electrical contact performance, and meets the requirements of electrical equipment for electrical conductivity. As a low-melting-point metal, silver can effectively improve the wear resistance, corrosion resistance and oxidation resistance of the entire composite material, improve the overall performance of the electrical contact, and extend its service life. The thickness of the silver layer is calculated according to the actual product composition and can be flexibly adjusted to meet the requirements for conductivity, wear resistance and oxidation resistance in different applications, thereby achieving precise design and optimization. The silver layer can effectively isolate the high-melting-point metal below from contact with the environment, prevent the intrusion of oxygen and corrosive substances, and thus improve the material's oxidation resistance in high temperature or harsh environments. The silver layer can not only improve the physical properties of the material, but also increase the beauty of the product, enhance market competitiveness, and meet customer requirements for appearance quality. The deposition of the silver layer can increase the surface hardness of the bulk metal ab mixture, reduce wear and mechanical damage, and improve the reliability of the product in the working environment. The silver layer may form a certain degree of alloying at the interface with the high melting point metal, which improves the interfacial bonding strength of the electrical contact and helps to ensure the stability and durability of the product under high load conditions.
[0055] Embodiment 1
[0056] (1) Soak the metal tungsten powder in concentrated nitric acid at 80°C for 30 seconds, wash and dry to obtain the treated tungsten powder;
[0057] (2) The treated tungsten powder is placed in a 200-ton hydraulic press to be pressed into shape. After 30 minutes, it is pressed again in a 300-ton hydraulic press to obtain a tungsten skeleton plate with a thickness of 2 mm.
[0058] (3) Place a 2 mm thick tungsten skeleton plate at the cathode of the electrolytic cell, with a weighing and metering device. The electrolytic mother liquid is a silver nitrate solution with a solution temperature of 55-70°C. The anode plate is a 99.99% pure silver plate. The current density of the electrolytic cell is controlled to be 100-110 A / m 2 ;
[0059] (4) Setting the weighing and measuring device of the cathode of the electrolytic cell to automatically stop the electrolysis when it detects that the weight of the silver tungsten plate is 1.538 times the weight of the initial tungsten skeleton plate;
[0060] (5) The cathode silver tungsten plate of the electrolytic cell is taken out of the electrolytic cell, cleaned and dried, and then cut into product sizes of 10 mm × 8 mm × 2 mm using a laser. The cut products are then subjected to melt infiltration, re-pressing and post-processing to obtain the desired finished AgW65 product.
[0061] Embodiment 2
[0062] (1) Soak the metal tungsten carbide powder in concentrated nitric acid at 80°C for 20 seconds, wash and dry to obtain the treated tungsten carbide powder;
[0063] (2) The treated tungsten carbide powder is placed in a 200-ton hydraulic press to be pressed into shape. After 30 minutes, it is repeatedly pressed with a 300-ton hydraulic press to obtain a tungsten carbide skeleton plate with a thickness of 3.5 mm;
[0064] (3) Place a 3.5 mm thick tungsten carbide skeleton plate at the cathode of the electrolytic cell. There is a weighing and metering device. The electrolytic mother liquid is a silver nitrate solution with a solution temperature of 55-70°C. The anode plate is a silver plate with a purity of 99.99%. The current density of the electrolytic cell is controlled to be 200-210A / m 2 ;
[0065] (4) Setting the weighing and measuring device of the cathode of the electrolytic cell to automatically stop the electrolysis when it detects that the weight of the silver tungsten carbide plate is twice the weight of the tungsten carbide skeleton plate;
[0066] (5) The cathode silver tungsten plate of the electrolytic cell is taken out of the electrolytic cell, cleaned and dried, and then cut into product sizes of 11 mm × 9 mm × 3.5 mm using a laser. The cut products are then infiltrated, re-pressed, and post-processed to obtain the desired finished AgWC50 product.
[0067] The above disclosure is only the preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.
[0068] Although the invention has been described with reference to several specific embodiments, it should be understood that the invention is not limited to the specific embodiments disclosed. The invention is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the appended claims.
Claims
1. An internal oxidation method silver metal oxide electrical contact material, characterized in that: The following steps are involved: S1, subjecting high melting point metal powder a to chemical etching treatment, and then washing and drying to obtain powder a1; S2, pressing the powder a1 into a block a2 using a press; S3, using the block a2 as the cathode of the electrolytic cell, preparing the electrolytic mother solution with the low-melting-point metal b1, and using the high-purity low-melting-point block metal b2 as the anode, and applying power for electrolysis; S4, after several hours of electrolysis, the power is turned off and the cathode block metal ab mixture is taken out of the electrolytic cell; S5, washing and drying the bulk metal ab mixture and cutting it into product size by laser; S6. The cut products are subjected to melt infiltration, re-pressing and post-processing to obtain the desired finished products.
2. The internal oxidation silver metal oxide electrical contact material according to claim 1, characterized in that: In step S1, the high melting point metal powder a is one or more of tungsten, molybdenum, tungsten carbide and the like.
3. The internal oxidation silver metal oxide electrical contact material according to claim 1, characterized in that: In step S1, the chemical etching treatment is performed by using hot concentrated nitric acid for 0.1-5 minutes.
4. The internal oxidation silver metal oxide electrical contact material according to claim 1, characterized in that: In step S2, the thickness of the block a2 is pressed to the required product size thickness.
5. The internal oxidation silver metal oxide electrical contact material according to claim 1, characterized in that: In step S3, the electrolytic cell current density is 50-500A / m 2 .
6. The internal oxidation silver metal oxide electrical contact material according to claim 1, characterized in that: In step S3, the low melting point metal is one or more of silver, copper, gold and the like.
7. The internal oxidation silver metal oxide electrical contact material according to claim 1, characterized in that: In step S4, after the electrolysis stops, a silver layer is coated on the surface of the bulk metal ab mixture, and the thickness of the silver layer is calculated according to the actual product composition.
Citation Information
Patent Citations
Reinforced phase gradient distribution infiltrated silver-based electric contact material and preparation method thereof
CN108015276A